2016
DOI: 10.1177/1082013216629262
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, sensory, and nutritional quality of fresh-cut “Rojo Brillante” persimmon affected by maturity stage and antibrowning agents

Abstract: To prevent enzymatic browning of fresh-cut 'Rojo Brillante' persimmon, different combinations of ascorbic acid (AA) and citric acid (CA) with calcium chloride (CaCl) were tested in fruit harvested at two maturity stages (MS1 and MS2). Color, firmness, sensory quality, total vitamin C, radical scavenging activity, total phenolic content, and carotenoids were evaluated over nine days of storage at 5 ℃. Antibrowning dips reduced enzymatic browning if compared with the control samples. Selecting fruits with good f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…In contrast, a carrageenan‐based coating did not improve apple firmness and the addition of citric acid induced tissue softening. Previous work with fresh‐cut ‘Rojo Brillante’ persimmon showed that acidic anti‐browning agents such as citric or ascorbic acid, although effective in preventing enzymatic browning, led to major tissue softening and their combination with CaCl 2 was required to prevent excessive softening and maintain firmness within the same range than the control samples …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a carrageenan‐based coating did not improve apple firmness and the addition of citric acid induced tissue softening. Previous work with fresh‐cut ‘Rojo Brillante’ persimmon showed that acidic anti‐browning agents such as citric or ascorbic acid, although effective in preventing enzymatic browning, led to major tissue softening and their combination with CaCl 2 was required to prevent excessive softening and maintain firmness within the same range than the control samples …”
Section: Resultsmentioning
confidence: 99%
“…Harvested cauliflowers were dipped in 2% CaCl 2 at 40 • C to extend their shelf life and maintain freshness [48]. The 'Rojo Brillante' persimmon exhibited increased antioxidant levels and antioxidase activity, as well as reduced browning, when treated with 10 g/L citric acid together with 10 g/L CaCl 2 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Many developmental and environmental stimuli induce increases in cytoplasmic Ca 2+ , which lead to various physiological and downstream responses. Some studies have investigated the use of Ca 2+ treatments in preventing the browning of fruits and vegetables, but the effect of calcium chloride on enzymatic browning has not yet been studied in relation to luffa [26,27]. Our study explored the effect of Ca 2+ on fresh-cut luffa and the physiological mechanisms underlying this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Akyldiz et al (2004) used sensory evaluation to determine avor, astringency and skin color of dehydrated 'Türkay' persimmons. Sanchís et al (2016) also applied sensory evaluation together with physicochemical attributes to evaluate the quality of minimally processed 'Rojo Brillante' persimmons after anti-browning treatment. Das and Eun (2021) tested sensory astringency and evaluated the quality attributes of persimmons subjected to freezing temperatures.…”
Section: Introductionmentioning
confidence: 99%